Supporting learners in the transition from block-based to text-based programming, a systematic review - Strong, Glenn; Bresnihan, Nina; Tangney, Brendan (Journal of computer languages (Online), 2025)
This paper describes a systematic review of the approaches being taken to providing support to learners as they transition from block-based programming environments to text-based ones. It identifies and analyses the literature in the area, identifies the themes which are common across the different approaches being used, and determines gaps in the literature. With the widespread use of block-based programming environments in introductory programming education, the question of how to support learners in the transition to text-based environments has received much attention. The contribution of this paper is to analyse and characterise the approaches being taken to support learners by considering the question: what approaches have been developed to facilitate the transition from block-based programming to text-based programming for learners? To answer this, a systematic literature review was undertaken, combining manual and automatic searches to identify work in the field. A thematic analysis of the literature found eight themes covering technical and non-technical approaches to supporting transition, prompting a set of recommendations for gaps to be addressed in future development in the field. •Retaining knowledge of event-driven and concurrent programming supports engagement•Highlighting connections between block and text representations supports transfer•Motivation is improved by making tasks meaningful and authentic to the learner•Technical and pedagogical support must be combined carefully to complement each other•Further robust experimental data must improve the evidence base for future designs